2011
DOI: 10.1258/ebm.2010.010277
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella-mediated gene therapy in experimental colitis in mice

Abstract: Bacterial gene therapy - bactofection is a simple and effective method to deliver plasmid DNA into target tissue. We hypothesize that oral in vivo bactofection can be an interesting approach to influence the course of inflammatory bowel diseases. The aim of this study was to prove the effects of antioxidative and anti-inflammatory bactofection in dextran sulfate sodium (DSS)-treated mice. Attenuated bacteria Salmonella Typhimurium SL7207 carrying plasmids with genes encoding Cu-Zn superoxide dismutase and an N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…This line of thinking has lead to the emergence of probiotics for both the prophylactic prevention and treatment of gastrointestinal inflammatory diseases. In an extremely exciting line of investigation, evidence suggests that transgenic probiotic bacteria may serve as a method of reducing manipulating apoptosis and inflammation [124,125]. While this a promising therapeutic approach, there may be some apprehension towards the delivery of transgenic bacteria to compromised individuals.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This line of thinking has lead to the emergence of probiotics for both the prophylactic prevention and treatment of gastrointestinal inflammatory diseases. In an extremely exciting line of investigation, evidence suggests that transgenic probiotic bacteria may serve as a method of reducing manipulating apoptosis and inflammation [124,125]. While this a promising therapeutic approach, there may be some apprehension towards the delivery of transgenic bacteria to compromised individuals.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The pioneering work of Steidler and colleagues introduced genetically engineered Lactococcus lactis that produces IL-10 to DSS-treated mice, reducing the incidence of colitis by 50% [167]. Another study using weakened Salmonella Typhimurium SL7207 carrying superoxide dismutase and anti-inflammatory peptides showed some benefits in a murine colitis model [168]. Along with this line, Hamady and colleagues constructed a stain of Bacteriodes ovatus, an anaerobe that adheres to the mucus layer, to secrete KGF2 [169].…”
Section: Other Approaches To Manipulate Enteric Floramentioning
confidence: 99%
“…67,68 In the last few decades, bacteria-mediated gene therapy has attracted the interest of researchers due to its wide applications. Palffy et al 69,70 used an approach called bactofection in their study. They analyzed the effects of salmonella-mediated gene therapy using attenuated bacteria Salmonella typhimurium SL7207 carrying plasmids with genes for SOD1 and 7ND genes in DSS-induced colitis.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Results showed that the salmonella-mediated antioxidative and anti-inflammatory gene therapy is able to ameliorate colitis in both mice and rats. 69,70 Also under active investigation is stem cell therapy and its use in IBD. It has been proved in several experimental studies in rodents.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%